Under the sign of the cross: the people's salvation cathedral and the church-building industry in postsocialist Romania - Tateo, Giuseppe (Space and place, 2020)
"Based on extensive ethnographic research, this book investigates the construction of the world's highest Orthodox cathedral in Bucharest, Romania. Through the notion of re-consecration, the book brings together sociological and anthropological scholarship on eastern Christianity, secularization, post-socialist urban change and nationalism in a vivid account of societal transformation. The book identifies the structures of political and economic power, which allowed its fast construction, and why the state wanted such a religious revival of the urban space"--